(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2025)
The new technological system of the contemporary state has led to a new socio-ecological and educational model. The most obvious forms of modernization are open global trade markets and the globalization of cultures and educational philosophies within a new global space. Based on this logic, the university seeks, through its educational system, to align and harmonize with society’s technological environment and digitize its educational systems. Accordingly, university education has become more preoccupied with personal and specialized technologies and with regard to developing cognitive or professional attainment in the digital age. In this context, educational activities at the university have become primarily based on the principle of competence and the development of human resources within a competitive educational framework, emphasizing the "instrumental mind" as the basic model of rationality.